Transcriptome analysis of non human primate-induced pluripotent stem cell-derived cardiomyocytes in 2D monolayer culture vs. 3D engineered heart tissue. Issue 9 (1st October 2020) - Yang, Huaxiao; Shao, Ningyi; Holmström, Alexandra; Zhao, Xin; Chour, Tony; Chen, Haodong; Itzhaki, Ilanit; Wu, Haodi; Ameen, Mohamed; Cunningham, Nathan J; Tu, Chengyi; Zhao, Ming-Tao; et al.
Abstract: Aims: Stem cell therapy has shown promise for treating myocardial infarction via re-muscularization and paracrine signalling in both small and large animals. Non-human primates (NHPs), such as rhesus macaques ( Macaca mulatta ), are primarily utilized in preclinical trials due to their similarity to humans, both genetically and physiologically. Currently, induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) are delivered into the infarcted myocardium by either direct cell injection or an engineered tissue patch. Although both approaches have advantages in terms of sample preparation, cell–host interaction, and engraftment, how the iPSC-CMs respond to ischaemic conditions in the infarcted heart under these two different delivery approaches remains unclear. Here, we aim to gain a better understanding of the effects of hypoxia on iPSC-CMs at the transcriptome level. Methods and results: NHP iPSC-CMs in both monolayer culture (2D) and engineered heart tissue (EHT) (3D) format were exposed to hypoxic conditions to serve as surrogates of direct cell injection and tissue implantation in vivo, respectively. Outcomes were compared at the transcriptome level. We found the 3D EHT model was more sensitive to ischaemic conditions and similar to the native in vivo myocardium in terms of cell–extracellular matrix/cell–cell interactions, energy metabolism, and paracrine signalling. Conclusion: By exposing NHP iPSC-CMs to different culture conditions, transcriptome profiling improves our understanding of the mechanism of ischaemic injury.